Pb accumulation in spores of arbuscular mycorrhizal fungi - Salazar, María Julieta (2018)
Heavy metal (HM) pollution of soils is one of the most important and unsolved environmental problems affecting the world, with alternative solutions currently being investigated through different approaches. Arbuscular mycorrhizal fungi (AMF) are soil inhabitants that form symbiotic relationships with plants. This alleviates HM toxicity in the host plant, thereby enhancing tolerance. However, the few investigations that have addressed the presence of metals in the fungus structures were performed under experimental conditions, with there being no results reported for Pb. The current study represents a first approximation concerning the capability of spores to accumulate Pb in the AMF community present in a Pb polluted soil under field conditions. Micro X-ray fluorescence was utilized to obtain a direct observation of Pb in spores, and the innovation of total reflection X-ray fluorescence was applied to obtain Pb quantification in spores. The AMF community included species of Ambisporaceae, Archaeosporaceae, Gigasporacea, Glomeraceae and Paraglomeraceae, and was tolerant to high Pb concentrations in soil. Pb accumulation in AMF spores was demonstrated at the community level and corroborated by direct observation of the most abundant spores, which belonged to the Gigasporaceae group. Spore Pb accumulation is possibly dependent on the AMF and host plant species.